Дослідження алгоритму оптимізації процесів на основі OKR методів у сфері управління проектами - Чудак, Ю. В. (ХНУРЕ, 2021)
The purpose of this work is to overview and analyze process optimization algorithm based on the OKR practices in project management, its advantages and disadvantages to propose a solution that allows graphical visualization and tasks, plans analysis, finding bottlenecks in the overall structure of the companyand its processes using the OKR methodology.
Науковий керівник – к.т.н., доцент Чуприна А.С.
Keywords: OKR методи; управління проектами